Motivational Interviewing improves caregiver self-efficacy in heart failure: a secondary outcome analysis of the MOTIVATE-HF trial. (2nd July 2022) - Locatelli, G; Zeffiro, V; Occhino, G; Rebora, P; Caggianelli, G; Ausili, D; Alvaro, R; Riegel, B; Vellone, E
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Center of Excellence for Nursing Scholarship, Rome, Italy. Background: Caregiver self-efficacy, which is caregiver confidence in her own abilities to help the patient in performing self-care, directly influences caregiver contribution (CC) to self-care, while acting as a mediator between predictors of CC to self-care and CC to self-care itself. Although caregiver self-efficacy is associated with patient and caregiver outcomes, evidence on interventions aiming to improve this variable, as well as CC to self-care, is scarce. Purpose: To evaluate the effect of Motivational Interviewing (MI) on caregiver self-efficacy and CC to self-care in heart failure. Methods: Secondary outcome analysis of the MOTIVATE-HF RCT. A total of 235 caregivers and 238 patients completed the study. Participants were recruited from three centres in Italy and randomized into Arm 1 (MI for patients), Arm 2 (MI for patients and caregivers), Arm 3 (standard care). The intervention consisted in one face-to-face MI session followed by three telephone contacts delivered to patients (Arm 1) or to patients and caregivers (Arm 2). Caregiver self-efficacy and CC to self-care were assessed with the Caregiver Contribution to Self-Care of HF Index. Data were collected at baseline, before the intervention, and after 3, 6, 9, 12 months from enrolment. Results: Among the three arms, caregivers median age was 55 years, they were mainly female (76%), married (72%), spouses (37%), employed (73.5%), with a high school level or higher education (55%), and living with the patients (60%). Patients median age was 74 years, they were mainly male (58%), retired (76%), in NYHA Class II (61.9%). Over the year of the study, caregiver self-efficacy significantly improved in all arms, and was significantly higher in Arm 2 compared to Arm 3 at 9-month follow-up (difference: 8.36, 95% CI (3.13; 13.59), p = 0.002). At 12-month follow-up, caregiver self-efficacy was still higher in Arm 2 compared to Arm 3, but this difference only approached statistical significance (difference: 6.59, 95% CI (-0.41; 13.60), p = 0.064). The longitudinal mixed linear model on self-efficacy, accounting for time, living with the patient, randomization arm and their interaction, confirmed a significantly higher improvement of caregiver self-efficacy in Arm 2 compared to Arm 3 (β ̂ = 1.39, 95% CI (0.02; 2.75), p = 0.046). CC to self-care significantly improved over time in all Arms, but without significant differences among the three Arms. Conclusion: Our results show that MI was effective in improving caregiver self-efficacy, but not CC to self-care. This may indicate that MI was able to improve how well caregivers were supporting patients, as showed by improvements in self-efficacy, but not how much they were doing it, as showed by the lack of improvement in CC to self-care. Further studies need to better understand how caregiver self-efficacy affects CC to self-care, how caregiver self-efficacy can be further improved, and the necessary intensity of MI to improve CC to self-care.